2023
DOI: 10.1093/forsci/fxad032
|View full text |Cite
|
Sign up to set email alerts
|

Partial Harvest Effects on the Forest Floor at Four Northern Hardwood Sites in the Green Mountains of Vermont, USA

Abstract: Harvesting activities are known to decrease forest floor carbon pools, but the response varies with harvest intensity. We examined partial harvesting (33–55% of basal area removed) effects on the forest floor at four northern hardwood sites in Vermont, USA. Six baseline quantitative samples were taken at each site and 9–36 new locations were sampled 1.5–2.6 years after harvesting. Forest soil disturbance was estimated, and basal area was tallied pre- and post-harvest. The forest floor consisted primarily of Oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Increasingly, the soil C literature is turning in this direction, with studies addressing more prevalent treatments such as single- and group-tree selection, crop tree release, various types of thinning, and shelterwood harvests. Two recent partial harvest studies, both in northern hardwoods, provide several nuanced insights that help advance the clearcutting-biased literature on this topic [ 83 , 84 ]. First, neither of these studies detected significant changes in total organic horizon C stocks (though Puhlick and Fernandez [ 83 ] reported fine-fraction O horizon declines).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasingly, the soil C literature is turning in this direction, with studies addressing more prevalent treatments such as single- and group-tree selection, crop tree release, various types of thinning, and shelterwood harvests. Two recent partial harvest studies, both in northern hardwoods, provide several nuanced insights that help advance the clearcutting-biased literature on this topic [ 83 , 84 ]. First, neither of these studies detected significant changes in total organic horizon C stocks (though Puhlick and Fernandez [ 83 ] reported fine-fraction O horizon declines).…”
Section: Discussionmentioning
confidence: 99%
“…First, we incorporated bulk density (Db) as a specific response parameter of interest. Second, in several cases, we directly contacted study authors to obtain data not reported in, but underpinning several forest harvest papers from the region [ 73 , 83 , 84 , 87 , 88 ]. These personal communications were necessary to bring summarized data from these important regional papers to the same level of site-specific detail found in the majority of other forest harvest papers (or their associated Additional file 2 : Datasets).…”
Section: Methodsmentioning
confidence: 99%